Research on stem cell therapy for spinal cord injury: a bibliometric and visual analysis from 2018–2023 - Liu, Ruxing; Peng, Bo; Yuan, Jie; Hu, Jiahao; Yang, Jianxin; Shan, Nan; Li, Qichao; Zhao, Bin; Xu, Chaojian; Wang, Yongfeng (Frontiers in Genetics, 2024)
Objectives: The aim of this study was to conduct a bibliometric analysis of the literature on stem cell treatment for spinal cord injury to gain an intuitive understanding of how the field is progressing, discover topics of interest, and determine what development trends are emerging in this field. Background: Spinal cord injury and its complications often cause an enormous economic burden, and postinjury repair and treatment have always been challenging in clinical and scientific research. Stem cell therapy for spinal cord injury can prevent immune rejection and induce the release of neuroprotective and anti-inflammatory factors to reduce the production of stress-related proteins, reactive oxygen species, and inflammatory reactions. Methods: We analyzed the number and quality of publications in the field of stem cell therapy in spinal cord injury between 2018.01.01 and 2023.06.30 in the core collection database of Web of Science. CiteSpace and VOSviewer were used to sort and summarize these studies by country, institution, authors' publications, and collaborative networks. In addition, the research topics of interest were identified and summarized. Results: This study ultimately included 2,150 valid papers, with the number of publications showing a gradual upward trend. The country, institution, author and journal with the greatest number of publications and citations are China, the Chinese Academy of Sciences, Dai JW, and the International Journal of Molecular Sciences, respectively. The top three high-frequency keyword clusters were hereditary paraplegia, reactive astrocytes and tissue engineering. Conclusion: With the help of visual analysis, we identified general trends and research topics of interest in the field of spinal cord injury over the last 5 years. Our findings suggest that stem cell transplantation for spinal cord injury and exosome therapy may be a focus of future research. This study provides a foundation for future research on stem cell therapy as well as clinical efforts in this field.